Heart rate variability in healthy adolescents at rest - Vanderlei, Franciele Marques; Rossi, Renata Claudino; de Souza, Naiara Maria [UNESP]; de Sá, Denise Aparecida [UNESP]; Gonçalves, Tatiana Mangetti [UNESP]; Pastre, Carlos Marcelo [UNESP]; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (My University, 2012)
Objective: to describe the cardiac autonomic function in healthy adolescents between 13 and 18 years old. Methods: data from 93 adolescents, of both sexes, were analyzed; they were divided into three groups according to age. Group A 13-14 years old (n=26), Group B 15-16 years old (n = 30) and Group C 17-18 years old (n = 17). The protocol consisted of raising the heart rate, beat by beat for twenty minutes of rest in supine position with spontaneous breathing. The cardiac autonomic behavior analysis was performed by the method of heart rate variability (HRV) through the indices of the Poincaré plot (SD1, SD2 and ratio SD1/SD2) and its qualitative analysis and indices in linear time domain (RMSSD and SDNN) and frequency (LFnu, HFnu and LF/HF). One-way ANOVA test or Kruskal-Wallis test was used for comparison between groups, with a significance level of 5%. Results: there was no significant difference in none of the indices compared the three groups. In addition,visual analysis of Poincaré plot has observed for all age groups large dispersion of RR intervals, indicating that these groups have good HRV. Conclusion: there were no changes in HRV in the different age groups analyzed, however the result allowed to establish a standard for each group that was studied, becomes an important tool for comparison of cardiac autonomic function between healthy and patients subjects or in different areas.
Keywords: Adolescent; Autonomic nervous system; Cardiology; Heart rate